2020
DOI: 10.1016/j.psychres.2020.113306
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and predictors in patients with borderline personality disorder during the COVID-19 outbreak: A 2.5-month naturalistic exploratory study in Spain

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 2 publications
1
18
0
2
Order By: Relevance
“…Multiple studies in patients with Obsessive Compulsive Disorder (OCD) demonstrated a substantial increase in obsessions and compulsions since the outbreak ( Benatti et al, 2020 ; Davide et al, 2020 ; Sulaimani and Bagadood, 2020 ). In contrast, the outbreak and measures did not impact the mental wellbeing of elderly patients with major depression disorder or patients with borderline disorder ( Álvaro et al, 2020 ; Hamm et al, 2020 ).…”
Section: Introductionmentioning
confidence: 86%
“…Multiple studies in patients with Obsessive Compulsive Disorder (OCD) demonstrated a substantial increase in obsessions and compulsions since the outbreak ( Benatti et al, 2020 ; Davide et al, 2020 ; Sulaimani and Bagadood, 2020 ). In contrast, the outbreak and measures did not impact the mental wellbeing of elderly patients with major depression disorder or patients with borderline disorder ( Álvaro et al, 2020 ; Hamm et al, 2020 ).…”
Section: Introductionmentioning
confidence: 86%
“…Enriching understanding of components of successful prevention and treatment, and developing more accessible treatments for personality disorder that can be delivered early in the symptom trajectory has been recognised as a national mental health priority area in Australia (NHMRC, 2012 ). Given the effect that the COVID-19 global pandemic has had on mental illness risk in the general population ( e.g ., Serafini et al , 2020) and individuals with pre-existing mental health conditions and personality disorders specifically (Álvaro et al , 2020 ; Yao et al , 2020 ) providing effective online therapy has clear implications for mitigating symptom progression and improving access for those who are geographically isolated. As such, flow on research generated by this review has potential to impact health and wellbeing for adolescents with personality disorder or emerging personality disorder symptoms, and their carers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to address how therapy can be accessible and helpful for more individuals with personality disorder. For some individuals, location and resources limits accessibility and given the increasing use of digital technology in young people’s lives, online therapy could be used to overcome these barriers (Clark, Kuosmanen, & Barry, 2015) The international coronavirus disease 2019 (COVID-19) pandemic has led to an even more urgent need to deliver online psychotherapy as it has placed strain on the ability to provide face-to-face therapy to individuals with personality disorder (Álvaro et al , 2020 ). People with existing mental health conditions are particularly vulnerable to anxiety, feelings of uncertainty and social isolation that COVID-19 mitigation measures have entailed (Sher, 2020 ; Yao, Chen, & Xu, 2020 ), motivating a push for greater access to telehealth and internet therapy (Zhou et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in particular and a subjectively experienced lack of agency and control over circumstances are significant causes of distress, especially in patients with BPD, leading to more pronounced difficulties in emotion regulation, impulsive and risk-taking behaviours (Mortensen, Evensmoen, Klensmeden, & Håberg, 2016;Pakpour & Griffiths, 2020). Social isolation, financial hardship, exposure to domestic violence, substance misuse, uncertainty about easing of restrictions, worry about significant others or bereavements, limited access to means and irresponsible media reporting have all been identified as challenges in the current situation (Álvaro et al, 2020;Polizzi, Lynn, & Perry, 2020). In addition, even for those currently in treatment, the necessary changes in therapy delivery -remote sessions -may impact BPD patients.…”
Section: Introductionmentioning
confidence: 99%